Impossible Presence: Toward a Queer Singapore Cinema, 1990s–2000s - Chan, Kenneth (Queer Singapore : Illiberal Citizenship and Mediated Cultures, 2012)
The writer frames his analysis of Kan Lume and Loo Zihan's feature length film Solos (2007) with a historical overview of the representation of queer sexualities in new Singaporean cinema. This approach also takes in the Penal Code Section 377A, arguing that not only do these repressive laws force queer sexualities to the margins of culture and society, but also that the State's censorship laws are a means by which it can reify ‘the Asian value system's supposed rejection of queerness’.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé